Determining relevant petiole anatomy characters to delimit Eupolypods I families - JEANETTE MARA P. TAN; INOCENCIO E. BUOT, JR. (Society for Indonesian Biodiversity, 2020)
Abstract. Tan JMP, Buot Jr. IE. 2020. Determining relevant petiole anatomy characters to delimit Eupolypods I families. Biodiversitas 21: 2721-2726. The delineation of the families under eupolypods I has been quite challenging. With that, characters that are stable and taxonomically significant are necessary. The study attempted to use petiole anatomy characters to study the taxonomy of the eupolypods I families. Fresh eupolypods I representatives were collected from the field and were fixed with formalin-acetic acid alcohol (FAA). The petioles were cut and processed into permanent mounts using alcohol dehydration series and following standard microtechnique protocols. The petiole anatomy characters of the 21 representative species of eupolypods I were first studied of their stability and subjected to multiple correspondence analysis (MCA) to determine the most taxonomically relevant character. The MCA biplot showed that four petiole anatomy characters were useful to describe and delineate families of eupolypods I. These petiole anatomy characters included, xylem shape, vascular bundle shape, and number of vascular bundles.